Nicéphore Blemmydès: Œuvres théologiques. Tome 1. Edited by Michel Stavrou - Panagopoulos, Spyros (The journal of theological studies, 2010)
Monk–scholar, philosopher, and theologian, Nikephoros Blemmydes (1198–c.1269) is a grand intellectual personality of the Byzantine thirteenth century. His theological works, published in this first volume of the Sources chrétiennes edition, touch on several questions about the Holy Trinity and primarily the procession of the Holy Spirit. Blemmydes developed his reflection for about thirty years. By the use of the Greek Fathers, he offers a rich synthesis of the theology of the Holy Spirit in Byzantium between Photius and Gregory Palamas. Blemmydes reflects, on a second level, the dialogue with the Latins.